Analysis of the economic performance and competitiveness of the European Union countries - Bojnec, Štefan; Marčeta, Milja (Serbian Journal of Management, 2022)
The main purpose of this study is to identify the dynamics of economic performance and competitiveness in the European Union (EU-28) countries and their convergences over the two periods, 2008-2015 and 2015-2019. The comparative analysis is used to answer the research question with applied the hierarchical cluster analysis, Ward's method, and t-test to test the set hypothesis. Eurostat and World Economic Forum data were used for the period 2008-2019.The empirical results confirmed our hypothesis that there are convergences in the key indicators of trade openness, exports as % of gross domestic product (GDP), market shares as % in world trade, GDP per capita, and global competitiveness index. The study contributes to the empirical analysis on the existence of convergences in a group of indicators of economic performance, trade openness, and global competitiveness of the EU-28 countries. The common clusters were formed, and the set hypothesis was tested regarding the convergences of the EU-28 countries by means of a hierarchical cluster analysis. Trade openness and export market shares in world trade, and competitiveness of EU-28 countries are important for trade policies improving global competitiveness and improving convergences in the heterogeneity among the EU countries.
Keywords: trade openness; export market shares; level economic development; global competitiveness; European Union